Big data analytics quality model in enhancing healthcare organizational performance: a content validity study - Mohd Nasir, Wan Mohd Haffiz; Abdullah, Rusli; Jusoh, Yusmadi Yah; Abdullah, Salfarina (IEEE, 2023)
Big Data Analytics (BDA) has the potential to deliver a comprehensive answer with improved insights into the value of the data collected in the healthcare sector. An assessment of the quality of BDA is crucial to assure that the goal of BDA as the end-to-end solution in enhancing healthcare organizations is achieved. Thus, a holistic BDA Quality (BDAQ) model needs to be developed to achieve the goal. As part of the BDAQ model development processes, this paper will highlight the content validation study. In quantitative research, survey instrument validation is important. A group of ten experts, including two academicians, two specialists, one data scientist, two subject matter experts, a BDA expert, an industry expert, a senior ICT director in healthcare, and a content validity expert, provided the data. Based on the collected data, the scores were analyzed by incorporating the Item-Content Validity index (I-CVI) and modified kappa (K) statistics. From a collection of 62 items, the content validity process removed one item and retained 61 items, while the revised items continued for further analysis. These specific content validity findings suggest that the assessed instrument can be employed to establish a degree of content validity that is acceptable. Once the verification process and analysis are done, the pilot study on the BDAQ model will begin, followed by the validated BDAQ model through the actual study.